Soil resistivity influence due to the different utilization of electrical resistivity array - Zainal Abidin, Mohd Hazreek; Saad, Rosli; Wijeyesekera, Devapriya Chitral; Ahmad, Fauziah (2013)
Electrical resistivity method (ERM) was increasingly adopted as an alternative tool in shallow subsurface exploration by the geotechnical engineers. This study presents the influence of soil electrical resistivity value (ERV) due to the different types of electrical resistivity array used in practice. The dissimilarity of ERV has always become a popular argument by engineers to the geophysicist due to its less fundamental knowledge of electrical resistivity method. From past experienced, the fundamental of ERM was less being exposed by the engineer thus creating several black boxes of the ERM basic theory which importantly required during the data acquisition and processing stages. Hence, the result produced from the ERM was difficult to deliver in a sound of definitive ways due to lack of knowledge and experienced of most engineers. Hence, this study presents the influence of soil ERV due to the different types of array used with particular reference to Wenner, Schlumberger, Dipole-dipole and Pole-dipole. A line of electrical resistivity imaging was performed on small embankment of lateritic soil in loose condition with different types of array using ABEM SAS (4000) equipment set. Three in line of soil samples were tested for moisture content (w) test immediately after the electrical resistivity data acquisition was completely measured. Moreover, particle size distribution test using dry and wet sieve was also being performed in order support to the ERV findings. It was found that the ERV was different for each types of array used even it was performed on the same particular location of the survey line. However, it was found that there is a consistent relationship between ERV and moisture content results which can be represent by ERV ∞ 1/w. Hence, it was found that ERV can be influenced by types of array used during the field measurement despite of the physical and chemical influences. Each types of array were applicable in subsurface profile investigation which normally subjected to the several considerations such as object target and the maximum depth of interest investigated.